IMPLEMENTATION OF THE CREDIT AND MODULAR SYSTEM IN DIFFERENT CONTEXTS (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2026)
Methods of teaching a foreign language have undergone serious changes, as there has come a turning point in the study of the interaction of language and culture: the attention of linguists has shifted from the internal structure of the language to its functioning.